Caught Between the Notions of Ethnicity, Citizenship and Diaspora: The Case of the Bosniaks in Turkey - Coban, Melih (Poligrafi, 2021)
Along with many others, Bosniaks are an ethnic group within the contemporary Turkish nation with immigrant roots dating back to the last quarter of the 19th century. Constituting a significant ethno-demographic part of the Ottoman legacy within the modern Turkish nation, Bosniaks in Turkey have long refrained from identifying themselves with a separate ethnic or cultural identity when confronted with the assimilationist cultural policies of the new nation state. But, while adapting themselves to Turkish culture and identity, Bosniaks have also preserved a collective identity of Bosniakness, mostly owing to the fact that their population in Turkey has been fed by continuous migration waves in different periods. The aim of this study is to analyze the problematic development of a Bosniak identity in Turkey with regards to the cultural assimilation processes and continuous migration waves and other factors on both foreign and domestic scales. Based on the findings of the study, it can be concluded that Bosniaks in Turkey do not yet constitute a Bosniak diaspora, but rather they can be regarded as a diaspora in the making.